PENGARUH JAM OPERASIONAL, LOKASI DAN JENIS DAGANGAN TERHADAP PENDAPATAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Hafizh Azzam Hilmy; Joko Utomo; Mamik Indaryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Street vendors play an important role in the urban economy, including in Semarang City, where street vendor growth continues to increase from year to year. The role of street vendors not only helps drive the economy, but also provides jobs for people who may have difficulty accessing the formal sector. Previous research data reported that there was a significant difference of up to 3 times the average income of the lowest street vendors compared to the highest, with a difference in average daily income of ± Rp. 200,000.00 and the average monthly income of the highest to the lowest having a difference of ± Rp. 5,500,000.00 in differences in operating hours, location, and type of merchandise. From the difference in income, there are street vendors who have incomes below the UMR of Semarang City. Researchers are interested in seeing how the variables of operating hours, location, and type of merchandise affect the income of street vendors in Semarang City by considering the UMR of Semarang City. This type of research is quantitative descriptive with 100 street vendor samples in Semarang City from various locations. The data collected was then analyzed using SPSS. The results of this study are that operating hours, location, and type of merchandise have a significant positive effect partially on the income of street vendors in Semarang City with the T Test and F Test, from the results of the determination coefficient test R2 of 0.515 which means that the variation in street vendor income is influenced by operating hours, location and type of merchandise by 51.5%, while the remaining 48.5% is influenced by other variables outside this study.